Internalisasi Nilai Sosial Keislaman melalui Outing Class di Masjid Islamic Center Mataram pada Siswa SDN 3 Bengkel Lombok Barat - Murdianto Murdianto (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Internalization of Islamic Social Values through Outing Class at the Mataram Islamic Center Mosque among SDN 3 Bengkel Lombok Barat Students. This study analyzes the internalization of Islamic social values through an outing class conducted at the Mataram Islamic Center Mosque. Using a descriptive qualitative case-study approach, data were collected through observation, interviews, and documentation involving elementary students, Islamic education teachers, and activity facilitators. The findings show that outing class enables students to experience Islamic values contextually through prayer practice, hajj simulation, disciplined participation, and guided social interaction in a mosque environment. The mosque functions not only as a worship space but also as an educational and socialization arena where students learn adab, discipline, cooperation, and responsibility. Teachers play a central role as agents of value internalization through hidden curriculum, modeling, habituation, and corrective guidance. The study concludes that outing class can serve as a contextual and applicative model of Islamic education that integrates cognitive, affective, and psychomotor learning for strengthening students’ religious character.